Factors influencing purchase intention in e‐commerce: the case of online consumers of travel - Pereira, Francisca Marques de Sousa Caetano (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence